2000
DOI: 10.1002/1097-4628(20001024)78:4<829::aid-app160>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Fourier transform infrared/differential scanning calorimetry system used to study the different thermal behaviors of polymethacrylate copolymers of eudragits RS, RL, E 30D, or E

Abstract: The thermal stability of Eudragits RL, RS, E 30D, and E films was qualitatively investigated by the reflectance Fourier transform infrared microspectroscopy equipped with differential scanning calorimetry (FTIR/DSC microscopic system). DSC and thermogravimetric analysis (TGA) were also used to study the thermal behavior of the granules of the raw material and the film of these polymers. The results indicate that the Eudragit RL, RS, or E 30D polymer exhibited a higher thermal‐stable behavior, but Eudragit E ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…The melt viscosity of pure EPO is one order of magnitude larger at all melt temperatures than that of with API (and plasticizer) content. An extrapolation indicates that MES temperature of EPO would be over 180°C, at which, however, a severe decomposition reaction is induced, thus EPO is not convenient for MES as a pure polymer. The addition of CAR alone to the polymer lowered, however, the viscosity dramatically, enabling fiber formation at a reduced 155°C temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The melt viscosity of pure EPO is one order of magnitude larger at all melt temperatures than that of with API (and plasticizer) content. An extrapolation indicates that MES temperature of EPO would be over 180°C, at which, however, a severe decomposition reaction is induced, thus EPO is not convenient for MES as a pure polymer. The addition of CAR alone to the polymer lowered, however, the viscosity dramatically, enabling fiber formation at a reduced 155°C temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Table , the impurities could be precisely determined according to the small deviations between the repeated measurements. The polymeric matrix and the plasticizers can be considered as thermally stabile compounds used in practice . In order to differentiate between the thermal effects of extrusion and MES steps, the extrudates and the melt electrospun fibers were measured separately.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with literature reports. It is known that the T g of PDMAEMA and copolymers on the base of DMAEMA are below 100°C 30–32…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that Eudragit RL and RS are thermostable up to 167°C, and metoprolol is stable below 160°C, the process temperatures selected in this study were always below the onset of degradation of each component (3,18). In addition, DSC measurements were conducted up to 180°C on individual components and physical mixtures, and no evidence of thermodegradation was found in all thermograms.…”
Section: Processability Of Injection-moulded Eudragit Rl/rs Formulationsmentioning
confidence: 92%